Impaired Cognitive Function After Coronart Artery Bypass Graft (CABG) - Mukhammad Arif Hadi Khoiruddin (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2022)
Coronary artery disease is one of the most common causes of death worldwide. This disease can be treated with Coronary Artery Bypass Graft (CABG) surgery. CABG is one of the main treatment strategies for severe coronary artery disease. This procedure can cause various side effects, including Post Operative Cognitive Dysfunction (POCD). The purpose of this literature review is to determine cognitive function disorders that occur after CABG surgery. The benefit of writing this scientific paper is to explore the occurrence of POCD in coronary artery patients undergoing CABG procedures.